#### Answer

$x=-19$

#### Work Step by Step

$\bf{\text{Solution Outline:}}$
To solve the given equation, $
3(2x-2)-4(x+6)=3x+8+x
,$ use the Distributive Property. Then use the properties of equality to combine like terms and to isolate the variable.
$\bf{\text{Solution Details:}}$
Using the Distributive Property which is given by $a(b+c)=ab+ac,$ the equation above is equivalent to
\begin{array}{l}\require{cancel}
3(2x)+3(-2)-4(x)-4(6)=3x+8+x
\\\\
6x-6-4x-24=3x+8+x
.\end{array}
Using the properties of equality to combine like terms and to isolate the variable results to
\begin{array}{l}\require{cancel}
6x-6-4x-24=3x+8+x
\\\\
6x-4x-3x-x=8+6+24
\\\\
-2x=38
\\\\
x=\dfrac{38}{-2}
\\\\
x=-19
.\end{array}